Currículo: representações para os sujeitos da escola do campo na Maisa - Medeiros, Maria de Lourdes Fernandes de (2016)
The research has as object of study curriculum and realization of the same from the development of pedagogical practices of teachers of a school field, and how curriculum bias the themes: environment, technology and society. As the main problem of this research, we bring the question of how the curriculum take account of environmental, technological and social issues, from the action of teachers. To understand these relationships made a cut in high school, so the following objectives were defined: to compare from the teachers' relations with the Operational Guidelines of Rural Education, elements that are as specific nature of schools, from the point of view of these subjects on the appropriation of environmental issues, technological, social and cultural rights; identify how materializes the curriculum relationship with the environment, technology and society; verify the representations assigned to the school curriculum by teachers; analyze the narratives of teachers on the development of its pedagogical action, challenges and possibilities of the curriculum in practice. The method to develop this study was qualitative research and methodological strategy of action research. Select this type of research to be associated with various forms of collective action, so use the high school Pact meetings and educational and administrative meetings of the school to which they call "training course" In addition, we use the dialogue of teachers, which were recorded and filmed, observe classrooms, students heard, we analyze the school official documents and conducted an open interview with the director and educational coordinator of the school. We seek to identify the concepts and methodological strategies used by teachers to enable their projects on the subject. We use the training course as a source of study, so we can build an in-depth look about the actions carried out in schools, especially in 2015, producing an analysis of the representations that teachers and educational staff have about the curriculum and its relationship with practice pedagogical, at the intersection of this with the disciplinary and interdisciplinary. There were several issues discussed and different nuances, but one of the main results is that the school has a history of developed extra classroom activities in these moments she stands out, and in this context the teachers can engage students in an active, participatory and collaborative, these activities the curriculum can interbreed with environmental issues, technology and society, and the representations that the school has curriculum is a formal, hierarchical curriculum, however, when he brings this curricular action for teaching practice and / or didactic action, other movements are built